An evaluation model of the financial feasibility of social housing in urban redevelopment. Issue 2 (20th April 2015) - Tajani, Francesco; Morano, Pierluigi
Abstract : Purpose: – The purpose of this paper is to develop an evaluation model to support the decisions made by Public Administrations that influence urban regeneration and social housing to be implemented with the involvement of private investors. Design/methodology/approach: – Carried out with reference to an Italian regional territory, the model, subject to the constraint of financial feasibility for the private investor and the conditions of the local real estate market, allows to define: the maximum amount of social housing, as a percentage of the housing planned, to be sustained by the private investors; the administered price of sale and/or lease of the social housing; the exchange-factor of the area to be redeveloped. Findings: – The outcome of the research highlights the utility of the model as a tool to support the decisions made by Public Administrations in relation to urban planning. Practical implications: – The model, in addition to being simple to use, is extremely flexible and can be applied without any major changes in the structure and the type of information required in different spatial contexts. Social implications: – The work intends to contribute to the achievement of the European objectives of Horizon 2020 that, with the initiative named "Smart Cities and Communities", deals with urban themes and social issues, ensuring a strong economic impact of funded activities. Originality/value: – The proposed methodology allows to monitor the land use transformations and, since it is also applicable to historical and architectural buildings, it is an innovative system for the sustainable protection and promotion of cultural heritage as a driver of social cohesion as well as the creation of jobs.